Synthesis and characterization of activated carbon from the biomass of Saccharum bengalense for electrochemical supercapacitors. (December 2018) - Rawal, Sangeeta; Joshi, Bhawana; Kumar, Yogesh
Graphical abstract: Highlights: Saccharum bengalense or S. bengalense is used for the synthesis of activated carbon. S. bengalense derived activated carbon (SbAC)is used for supercapacitor application for the first time. SbAC shows good porous structure with high specific surface area value (2090 m 2 g −1 ). SbAC exhibits excellent charging/discharging cycle stability in aqueous electrolyte during 120, 000 cycles. Abstract: Low cost and very simple activation method (ZnCl2 as activating agent) is used for the synthesis of activated carbon derived from the biomass of Saccharum bengalense (S. bengalense) leaves. The S. bengalense derived activated carbon (SbAC) as the electrode material in Electric Double Layer Capacitors (EDLCs) is reported for the first time. The structural, surface morphological study and vibrational response of the SbAC are characterized by using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared Spectroscopy (FTIR), Raman spectroscopy, and Brunauer-Emmett-Teller (BET) surface area. Electrochemical studies indicate that the SbAC delivers the maximum specific capacitance of 102.6 F g −1 at scan rate of 2 mV/s in aqueous electrolyte (1 M Li2 SO4 ) for 1.6 V operating voltage. This high value of specific capacitance is credited to its high specific surface area (2090 m 2 g −1 ) and pore volume of 0.281 cm 3 g −1 . The SbAC exhibits good rate capability with an excellent charging/discharging cycle stability in aqueous electrolyte (1 M Li2 SO4 ) during 120, 000 cycles. The results indicate that SbAC shows good electrochemical properties to be used for energy storage applications in future.